Economic evaluation of health care : cautions for the developing country context - Skordis, Jolene (Centre for Actuarial Research (CARE), 2015)
Health economics has expanded enormously as a sub-discipline in the last four decades, drawing primarily on the theoretical foundations of welfare economics. The toolkit for the economic evaluation of health care now extends from the humble cost-minimisation exercise, through cost effectiveness measures, to the more complex cost utility or cost benefit models. These methodologies have differing strengths and drawbacks. This paper evaluates those attributes on both the practical and theoretical dimensions. On the practical dimension: The developing country context differs from the wealthier country context in a number of ways. This paper considers the differences in resource constraints and the differences in health priorities and asks to what extent the methodology is able to accommodate these variations. On the theoretical dimension: Few health care evaluations are conducted in a Pareto Optimal world. This paper considers the extent to which the welfare economic foundations of a methodology are successfully imported into its construction, and then how that foundation translates into its practical application.